Design Equations for a Closely-Spaced Two-Element Interferometer Including Internal Noise Coupling - Sutinjo, Adrian; McKinley, Benjamin; Belostotski, Leonid; Ung, Daniel CX; Thekkeppattu, Jishnu N
We present design equations for a two-element closely-spaced interferometer for measuring the noise temperature of a uniform sky. Such an interferometer is useful for observing highly diffuse radio sources such as the Milky Way and Cosmological signals. We develop a simple equivalent circuit based on radiophysics and antenna theory to describe the interactions between key design parameters such as antenna self and mutual impedance and noise parameters of the receiver; the latter is considered internal noise. This approach straightforwardly facilitates design studies as the response of the uniform signal and the systematic error due to internal noise coupling can be analyzed using the same equivalent circuit. The equivalent circuit shows that mutual coherence due to internal noise coupling is non-negligible and an inherent property of a closely-spaced interferometer. A realistic example design involving two closely-spaced horizontal dipoles over a lossy ground for Cosmological signal detection from 50 to 100 MHz is discussed as an illustration.